Measurement of Spatial Ability : Construction and Validation of the Spatial Reasoning Instrument for Middle School Students - Ramful, Ajay; Lowrie, Thomas; Logan, Tracy (Journal of psychoeducational assessment, 2017)
This article describes the development and validation of a newly designed instrument for measuring the spatial ability of middle school students (11-13 years old). The design of the Spatial Reasoning Instrument (SRI) is based on three constructs (mental rotation, spatial orientation, and spatial visualisation) and is aligned to the type of spatial maneuvers and task representations that middle- school students may encounter in mathematics and Science, Technology, Engineering and Mathematics (STEM)-related subjects. The instrument was administered to 430 students. Initially, a set of 15 items were devised for each of the three spatial constructs and the 45 items were eventually reduced to 30 items on the basis of factor analysis. The three underpinning factors accounted for 43% of variance. An internal reliability value of .845 was obtained. Subsequent Rasch analysis revealed appropriate item difficulty fit across each of the constructs. The three constructs of the SRI correlated significantly with existing well-established psychological instruments: for mental rotation (.71), spatial orientation (.41), and spatial visualisation (.66). The psychometric characteristics of SRI substantiate the use of this measurement tool for research and pedagogical purposes. [Author abstract]